Marine Debris of Northern Aceh Waters During First Monsoon Transition Period - Agustina, Sri; Karina, Sofyatuddin; Purnawan, Syahrul; Ondara, Koko (Graduate School of Universitas Syiah Kuala, 2024)
Pollution in the ocean caused by anthropogenic activities has been a global issue. However, data on marine debris in Aceh Waters is limited. This study was conducted to identify the category, density, and source of marine debris on the Weh Island and Aceh Island beaches during the first monsoon transition period. Samples were collected in April 2022 at four stations, namely Laweung Beach in Sumatra Island (station 1), Aron Beach in Weh Island (Station 2), Nipah Beach and Alue Riyeung Beach in Aceh Island (Station 3 and Station 4, respectively). Samples collected in a 100 m-length transect were classified into nine categories: plastic, foamed plastic, cloth, glass and ceramic, metal, paper and cupboard, rubber, wood, and others. The result depicted that the highest density was plastic (0.602-1.022 items/m2), followed by foamed plastic (0.038 to 0.654 items/m2) and rubber (0.020 to 0.089 items/m2). Turning to its appliances, plastic was mostly used as packaging, such as bottles and cups for drinking water, while foamed plastic and rubber were used for cooling boxes and footwear. As the sea current shifted during the monsoon transition period, trash from ships passing the marine routes around the Aceh Waters is assumed to be transporting debris from various countries, such as Malaysia, Thailand, and China.